(3JfXje GdTQcGJ GdJLGQjI (B:s (3TQcGJ GdCTNGU hTQcGJ GdCehGd (B/s - (3GdeUQj, YHGS eUWais ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2002)
(3GdeHGOF GdYGeI GdJj JMce GdTQcGJ(B-(3GdTQcI ef MjK GdWHjYI hGdfhY hGdTcd(B-(3GdVhGHW GdbGfhfjI dEfTGA GdTQcI(B-(3GdTQcI hacQI GdTNU GdeYfhj(B-(3GdVhGHW GdYGeI dEfbVGA GdTQcI(B-(3TQcGJ GdCTNGU(B-(3TQcGJ GdJVGef(B-(3TQcI GdJhUjI GdHSjWI(B-(3TQcI GdeMGUI(B-(3GdTQcGJ PGJ GdWGHY GdeNJdW(B-(3GdTQcI PGJ GdeSFhdjI GdeMOhOI(B-(3TQcI GdJhUjI HGdCSge(B-(3TQcGJ GdCehGd(B-(3TQcGJ GdeSGgeI(B-(3gjFGJ GdEOGQI aj TQcGJ GdeSGgeI(B-(3GfbVGA GdTQcI hbhGYO JUajJgGs
Keywords: (3GdTQcGJs; (3GdTQcGJ GdeSGgeIs; (3GdTQcGJ(B- (3GdJLGQIs